THE ROLE OF MATHEMATICS REALISTIC EDUCATION APPROACH ON STUDENTS’ MATHEMATICAL CRITICAL THINKING AND RESILIENCY - Murni, Sukma; Sugandi, Asep Ikin (IKIP SILIWANGI, 2018)
The purpose of this study is to analyze the role of mathematics realistic education (RME) approach on students’ mathematical critical thinking and resiliency. This study is an experiment with pre test-post test control group design and involves 62 eleventh grade students, a mathematical critical thinking test, a mathematical resiliency scale, and a perception on RME approach scale. The study found, on mathematical critical thinking ability (MCTA), its N Gain, and mathematical resiliency (MR) students getting treatment with RME approach attained better grades than the grades of students taught by conventional teaching. The first group students attained at medium grade level on MCTA and fairly good grade level on MR, while the second group students obtained at low grade level on MCTA, medium grade level on MR, and they realized difficulties in some items of mathematical critical thinking tasks. The other findings, there was no association between MCTA and MR, and students learned actively, thought critically and creatively, were unafraid to pose their opinion and performed to be self confident during RME approach.